Protein-protein interactions can be predicted using coiled coil co-evolution patterns. (7th January 2017) - Mier, Pablo; Alanis-Lobato, Gregorio; Andrade-Navarro, Miguel A.
Abstract: Protein-protein interactions are sometimes mediated by coiled coil structures. The evolutionary conservation of interacting orthologs in different species, along with the presence or absence of coiled coils in them, may help in the prediction of interacting pairs. Here, we illustrate how the presence of coiled coils in a protein can be exploited as a potential indicator for its interaction with another protein with coiled coils. The prediction capability of our strategy improves when restricting our dataset to highly reliable, known protein-protein interactions. Our study of the co-evolution of coiled coils demonstrates that pairs of interacting proteins can be distinguished from not interacting pairs by means of their structural information. This hints at the potential of our strategy to predict new protein-protein interactions. Highlights: The emergence of the coiled coils of interacting partners are correlated. Co-evolution of coiled coils indicates conservation of protein-protein interactions. Prediction capability of the approach relates to quality of experimental evidence. Paralog biases alone cannot explain the results. Our method will improve when a larger number of distributed proteomes are available.